2011
DOI: 10.1007/978-3-642-21663-3_48
|View full text |Cite
|
Sign up to set email alerts
|

Dialog Behaviors across Culture and Group Size

Abstract: Abstract. This study analyzes joint interaction behaviors of two-person and four-person standing conversations from three different cultures, American, Arab, and Mexican. To determine whether people use joint interaction behaviors differently in multiparty versus dyadic conversation, and how differences in culture affect this relationship, we examine differences in proxemics, speaker and listener gaze behaviors, and overlap and pause at turn transitions. Our analysis suggests that proxemics, gaze, and mutual g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…For instance, compared to dyads, groups exhibit different patterns of non-verbal behaviors (e.g. eye gaze) and communication ( Solano and Dunnam, 1985 ; Herrera et al , 2011 ), as well as different motivations to trust and cooperate with others ( Zhou and Zhang, 2006 ; Wildschut and Insko, 2007 ; Pereda et al , 2019 ). Indeed, groups of four may be the optimal group size for everyday collaborations as it maintains individual responsibility and efficacy ( Kameda et al , 1992 ), while enhancing collective action on behalf of a shared group identity ( Baumeister et al , 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, compared to dyads, groups exhibit different patterns of non-verbal behaviors (e.g. eye gaze) and communication ( Solano and Dunnam, 1985 ; Herrera et al , 2011 ), as well as different motivations to trust and cooperate with others ( Zhou and Zhang, 2006 ; Wildschut and Insko, 2007 ; Pereda et al , 2019 ). Indeed, groups of four may be the optimal group size for everyday collaborations as it maintains individual responsibility and efficacy ( Kameda et al , 1992 ), while enhancing collective action on behalf of a shared group identity ( Baumeister et al , 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The distance between individuals in a conversing group is an integral part of conversational behaviour and can affect other aspects of conversational style. Links have been found with the amount of conversational eye contact between them and different group sizes . Results from this study show that the distance between participants in a conversation decreased as the group went from a dyadic (two‐person) conversation to a multiparty conversation.…”
Section: Related Workmentioning
confidence: 75%
“…These observations merit further study. Because Herrera et al found that interpersonal distances change with group size, we also plan to evaluate whether the results for distance and orientation hold when they are applied in combination for different‐sized groups.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we note that discourse-analytic comparison of multiparty and dyadic conversation has indicated that differences as a function of the number of conversants vary across cultures [13]. Thus while the use of gaze to coordinate turn-transition differs between speakers of American English and of Mexican Spanish, for Americans this process is a function of group size: gaze plays a relatively smaller role in Mexican multiparty conversation than it does in American [13].…”
Section: Introductionmentioning
confidence: 76%
“…Finally, we note that discourse-analytic comparison of multiparty and dyadic conversation has indicated that differences as a function of the number of conversants vary across cultures [13]. Thus while the use of gaze to coordinate turn-transition differs between speakers of American English and of Mexican Spanish, for Americans this process is a function of group size: gaze plays a relatively smaller role in Mexican multiparty conversation than it does in American [13]. To explore the specific functional mechansisms for conversants' use of paralinguistic behaviors in multiparty conversation, in this study we oriented our study around four principle issues: whether grounding behaviors such as nodding get cued in ways similar to those observed in dyadic conversation, how the mechanisms of turn-transitions actually function, whether the presence of an artifact leads to changes in grounding behaviors, and how, if at all, these behaviors differ between speakers of American English and of Mexican Spanish.…”
Section: Introductionmentioning
confidence: 86%